Human Umbilical Mesenchymal Stromal Cells Mixed with Hyaluronan Transplantation Decreased Cartilage Destruction in a Rabbit Osteoarthritis Model - Yu-Hsun Chang; Dah-Ching Ding; Kun-Chi Wu (Stem Cells International, 2021)
Osteoarthritis (OA), the most common type of arthritis, causes pain in joints and disability. Due to the absence of ideal effective medication, stem cell transplantation emerges as a new hope for OA therapy. This study is aimed at evaluating the capability of human umbilical cord mesenchymal stromal cells (HUCMSCs) mixed with hyaluronan (HA) to treat osteoarthritis in a rabbit model. Differentiation capability of HUCMSCs, magnetic resonance image examination, and immunohistochemistry of the cartilage after transplantation of HUCMSCs mixed with HA in a rabbit OA model were explored. HUCMSCs exhibited typical mesenchymal stromal cell (MSC) characteristics, including spindle-shaped morphology, surface marker expressions (positive for human leukocyte antigen- (HLA-) ABC, CD44, CD73, CD90, and CD105; negative for HLA-DR, CD34, and CD45), and trilineage differentiation (chondrogenesis, adipogenesis, and osteogenesis). The gene expression of SOX9, type II collagen, and aggrecan in the HUCMSC-derived chondrocytes mixed with HA was increased after in vitro chondrogenesis compared with HUCMSCs. A gross and histological significant improvement in hyaline cartilage destruction after HUCMSCs mixed with HA was noted in the animal model compared to the OA knees. The International Cartilage Repair Society histological score and Safranin O staining were significantly higher for the treated knees than the control knees (p<0.05). Moreover, the expression of MMP13 was significantly decreased in the treated knees than in the OA knees. In conclusion, HUCMSCs mixed with HA in vitro and in vivo might attenuate the cartilage destruction in osteoarthritis. Our study provided evidence for future clinical trials.